2020
DOI: 10.3390/s20154237
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Nonlinear Model for Prediction of Frequency–Temperature Behavior of SAW Devices for Nanosensor Applications

Abstract: Surface acoustic wave (SAW)-based sensors have become highly valued for their use as nanosensors in industrial applications. Accurate prediction of the thermal stability is a key problem for sensor design. In this work, a numerical tool based on the finite element method combined with piezoelectric Lagrangian equations has been developed to accurately predict the thermal sensitivity characteristics of surface acoustic wave devices. Theoretical analysis for the geometric nonlinearity contributing to the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Finally, it should be noted that, when having access to highly advanced and expensive manufacturing facilities, finite element method (FEM) simulations can be used to develop a physically based model for SAW design optimization [ 36 , 37 , 38 , 39 ], in order to meet the specific application requirements. On the other hand, when using commercial devices, the user has access to only the information available in the datasheets.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be noted that, when having access to highly advanced and expensive manufacturing facilities, finite element method (FEM) simulations can be used to develop a physically based model for SAW design optimization [ 36 , 37 , 38 , 39 ], in order to meet the specific application requirements. On the other hand, when using commercial devices, the user has access to only the information available in the datasheets.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [9] discussed the nonlinear model for the SAW sensor using COMSOL Multiphysics tool to simulate the resonant frequency shift of the sensor for quartz and Lithium Tantalate substrates. They observed that the simulated results corroborated the simulated results for variation in cut angles, metallization ratio and electrode thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Surface acoustic wave (SAW) devices are used as resonators in electronic systems in a wide range of applications: mobile communications [ 1 , 2 ], sensors [ 3 , 4 ] and actuators [ 5 , 6 ], etc. Because of their excellent performance, including low insertion loss, high isolation, etc., filters and duplexers based on radio-frequency (RF) SAW resonators are mass-produced and widely used in current mobile phones [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%